Soluble TREM-1 as a diagnostic and prognostic biomarker in patients with septic shock: an observational clinical study. (2nd January 2017) - Brenner, Thorsten; Uhle, Florian; Fleming, Thomas; Wieland, Matthias; Schmoch, Thomas; Schmitt, Felix; Schmidt, Karsten; Zivkovic, Aleksandar R.; Bruckner, Thomas; Weigand, Markus A.; Hofer, Stefan
Abstract: Objectives: The impact of TREM-1-mediated inflammation was investigated in different inflammatory settings. Methods: Secondary analyses of an observational clinical pilot study, including 60 patients with septic shock, 30 postoperative controls and 30 healthy volunteers. Results: Plasma levels of sTREM-1 were found to identify patients with septic shock more effectively than procalcitonin and C-reactive protein. Moreover, sTREM-1 was identified to be an early predictor for survival in patients with septic shock. Conclusion: Due to its diagnostic as well as prognostic value in sepsis syndrome, implementation of sTREM-1 measurements in routine diagnostics should be taken into account.